Users’ awareness of fire safety in selected Pentecostal churches in Abuja, Nigeria - Olagunju, Omoniyi O.; Udeze, Dumebi R. (Frontiers in Built Environment, 2025)
Pentecostal megachurches represent some of the most densely occupied worship environments, where spatial configurations and collective behaviours can heighten fire-risk exposure and complicate evacuation dynamics. However, scholarly attention to congregant engagement with fire-safety provisions in these contexts remains limited. This study investigates fire-safety awareness, perceptions of system functionality, and confidence in emergency response among worshippers in four major Pentecostal churches in Abuja, Nigeria. The study employed a quantitative approach using structured questionnaires, which collected survey data from 325 participants. Descriptive and inferential statistical analyses of the data were used, which included frequency counts and percentages. The study reveals a general familiarity with exit routes and basic hazards but limited knowledge of formal evacuation protocols and reduced self-efficacy in operating fire-safety equipment. While active protection systems were viewed as functional and reliable, critical passive features such as fire doors, compartmentation, and smoke-control infrastructure were largely absent, resulting in an overreliance on mechanical systems. These findings underscore the need for structured fire-safety education, mandatory evacuation drills, and routine maintenance regimes, alongside the systematic incorporation of certified passive strategies into both new and retrofitted church facilities. The study advances fire-safety research by foregrounding the unique challenges of megachurch settings and calls for comparative, cross-denominational inquiry to evaluate how integrated active–passive approaches can enhance evacuation efficacy and occupant resilience.